TINJAUAN KETERSEDIAAN AIR BERSIH DI KECAMATAN SUAWAWA KABUPATEN BONE BOLANGO - Mato, Rahmit Aditya; Bakhtiar, Bakhtiar; Rachman, Ari Putra (Jurnal Teknik Sipil, Arsitek, Perencanaan Wilayah (J-TSIAP), 2023)
The research location was carried out in Suwawa District, Bone Bolango Regency using calculations so that this research was quantitative in nature. Based on the research results, normal domestic and non-domestic water needs in Ulanta Village, Bube Village and Bulodawa Village for the next few years (until 2020) are found to be 44.143 liters/second or 0.044 m3/second, while the maximum daily need for clean water is 0.086 m3/second, for peak hour demand in 2020 (5 year projection) it is found to be 0.131 m3/second. The availability of water in the Ulanta River in Suwawa District, calculated using the main discharge Q, is 1,917 m3/second. The relationship between water demand and water availability in the Ulanta river is still sufficient to meet normal water needs and the maximum water requirements required are 0.075 m3/sec < 1.917 m3/sec and 0.086 m3/sec < 1.917 m3/sec. Meanwhile, peak hour water demand is still sufficient with water availability, namely 0.131 m3/second < 1.917 m3/second. After carrying out this research, the researcher suggested that in future research to take more into account the stability of water flow which is a basic need for society, more specifically for the people of Suwawa District